2014
DOI: 10.1111/evo.12445
|View full text |Cite
|
Sign up to set email alerts
|

REPLICATED ORIGIN OF FEMALE-BIASED ADULT SEX RATIO IN INTRODUCED POPULATIONS OF THE TRINIDADIAN GUPPY (POECILIA RETICULATA)

Abstract: There are many theoretical and empirical studies explaining variation in offspring sex ratio but relatively few that explain variation in adult sex ratio. Adult sex ratios are important because biased sex ratios can be a driver of sexual selection and will reduce effective population size, affecting population persistence and shapes how populations respond to natural selection. Previous work on guppies (Poecilia reticulata) gives mixed results, usually showing a female-biased adult sex ratio. However, a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 84 publications
2
55
0
Order By: Relevance
“…This study adds to a growing literature suggesting that intraspecific variation may be important for shaping ecology [54][55][56]. Indeed, sexual dimorphism is one of the most common and well-known forms of intraspecific trait variation in the wild and many populations in nature show marked demographic differences in sex ratios from the commonly assumed expectation of 1 : 1 [2][3][4][5]7]. As such, we suggest that sex ratios may be a common driver of community and ecosystem variation across a wide diversity of organisms and habitat types.…”
Section: Resultsmentioning
confidence: 70%
“…This study adds to a growing literature suggesting that intraspecific variation may be important for shaping ecology [54][55][56]. Indeed, sexual dimorphism is one of the most common and well-known forms of intraspecific trait variation in the wild and many populations in nature show marked demographic differences in sex ratios from the commonly assumed expectation of 1 : 1 [2][3][4][5]7]. As such, we suggest that sex ratios may be a common driver of community and ecosystem variation across a wide diversity of organisms and habitat types.…”
Section: Resultsmentioning
confidence: 70%
“…Unequal parental roles might lead to biased sex ratios because the sexes engage unequally in parental duties, have different time budgets, and consequently experience different mortality rates (50). Accordingly, sex-biased mortality rates are often correlated with biased ASR across populations and species (51)(52)(53). Moreover, some authors suggest positive feedbacks between changes in ASR and parental sex roles and thus the relationship may even be bidirectional (8,23,54).…”
Section: Resultsmentioning
confidence: 99%
“…This contrasts with the majority of studies on various poeciliids (Vargas & Sostoa 1996;Cabral & Marques, 1999;Zúñiga-Vega et al, 2012) and specifically for H. bimaculata (Gómez-Márquez et al, 1999), which report female-biased population structure. Female-biased sex ratios in poeciliids arise typically because males are more susceptible to mortality from numerous factors such as predation, resource limitation, hypoxia and extreme temperatures, largely because they devote such high energetic allocations to courtship Rodd & Reznick, 1997;Pettersson et al, 2004;Arendt et al, 2014). Alternatively, Arendt et al (2014) suggested that differential mortality rates between sexes can bias snapshot analyses of sex ratios, depending on sampling season.…”
Section: Discussionmentioning
confidence: 99%
“…Female-biased sex ratios in poeciliids arise typically because males are more susceptible to mortality from numerous factors such as predation, resource limitation, hypoxia and extreme temperatures, largely because they devote such high energetic allocations to courtship Rodd & Reznick, 1997;Pettersson et al, 2004;Arendt et al, 2014). Alternatively, Arendt et al (2014) suggested that differential mortality rates between sexes can bias snapshot analyses of sex ratios, depending on sampling season. Long-term analysis of the demographics of predator-free poeciliid populations would help to better describe the effects of predation on sex ratios.…”
Section: Discussionmentioning
confidence: 99%